Potentiality of Mother Tongue Instruction and Multilingual Education Approach to Teaching English at Primary Level - Tamang, Dipak; Sigdel, Surya; Sharma, Mani Ram (PPSDP International Journal of Education, 2024)
The objectives of this study were to explore the participants’ lived experiences on medium of instruction while teaching English in the classrooms and to explore the participants’ lived experiences on Mother Tongue Based Multilingual Education approach to teaching English at primary level. Phenomenological research design was employed to complete this study. A set of questionnaires, interviews and discussion were the major research tools and three primary level English teachers were the sample population of this study. Phenomenological interviews and a set of questionnaires were used to collect the data. The collected data were transcribed, translated, coded and interpreted and analyzed thematically. The result of this study shows that a suitable medium of instruction is the most important factor and MTB-MLE approach is an effective approach to teach English language for the children of ethnic group people at pre-primary level. This study has implications for social change as teachers who engage in collaboration with colleagues and reflective practice will positively affect student achievement. Students may be taught by teachers who have the knowledge, skills, and attitude required for a successful implementation of a multilingual approach.